Daily fluctuation of genus Prevotella in porcine colon under ad libitum feeding and its association with nutrient substrates - Li, Yue; You, Jinwei; Liao, Yiyan; Wang, Dongfang; Wang, Hongyu; Su, Yong (Frontiers in Microbiology, 2025)
The circadian rhythms of the gut microbiota are biologically significant for the host. However, the association between fluctuations in the relative abundance of the microbiota and nutrient substrates in the gut remains incompletely understood. Using swine as a model, this study employed continuous sampling at 9 time points over 24 h via a colonic T-shaped fistula. It investigated the temporal dynamics of nutrient substrates and Prevotella abundance in the colon of pigs over a 24-h period and further explored dynamic interactions among KEGG level-3 pathways, genes, and Prevotella using metagenomic approaches. Results revealed a significant 24-h periodicity in Prevotella abundance, peaking at T06–T09 and declining to minimal levels at T18–T21, with the nadir at T18. Dynamic correlation network analysis uncovered significant temporal associations between Prevotella rhythms and nutrient substrates: negative correlations with true protein (TP) and ammonia nitrogen (NH₃-N), in contrast to positive correlations with starch and cellulose, exhibiting time lags ranging from −2 to 4 h. Prevotella copri exhibited high relative abundance and pronounced daily fluctuations, while Prevotella sp. MGM2 showed relatively high abundance but lacked daily fluctuations. Furthermore, differences existed in the dynamic correlations of genes and KEGG level-3 metabolic pathways of these two Prevotella species with nutrient substrates. The results revealed that the two Prevotella species in the colon exhibited different response strategies to nutrient substrates: Prevotella copri likely adopted a “rhythmic substrate-responsive strategy,” while Prevotella sp. MGM2 followed a “sustained response strategy,” which may explain their distinct daily fluctuations.